Digital Branding of Bank BJB Cibinong in Building BJB DIGI Awareness via Instagram - Tri Lestari, Martha; Natadisastra, Adhikara Candraraditya; Aziz, Rifqi Abdul (Jurnal Ilmiah Komunikasi Makna, 2024)
Bank BJB is the largest Regional Development Bank (BPD) in Indonesia. According to Bisnis.com, in the third quarter of 2023, bank BJB has the largest assets with an asset value of IDR 179.31 trillion, beating 9 national banks. This research discusses Bank BJB Cibinong's Digital Branding strategy which increases BJB DIGI awareness through Instagram. Bank BJB, the largest development bank in Indonesia with 65 branches, has a branch in Cibinong, West Java with a population of 5,643,838 in 2023. The aim is to analyze the use of Instagram @bankbjbcibinong in building awareness of BJB DIGI. Using a qualitative case study, data was collected via interviews and observations, analyzed using Digital Branding and New Media theory. The results show that Bank BJB Cibinong implemented a three-stage digital branding strategy: building credibility, increasing visibility, and creating a unique identity through promotional content, collaboration, mini vlogs, and philanthropic actions, with the support of the creative team. In conclusion, Bank BJB Cibinong is effective in utilizing Digital Branding for promotion and education, strengthening BJB DIGI awareness, but needs to increase the use of Instagram features and customer engagement.